An efficient and low resistant circumferential overlap trisection helical baffle heat exchanger with folded baffles. (1st April 2016) - Dong, Cong; Li, Dongshuang; Zheng, Youqu; Li, Guoneng; Suo, Yange; Chen, Yaping
Highlights: The novel cothHXf with circumferential overlap and folded baffles is first proposed. The key sections of cylindrical and dumbbell are constructed to analyze local flow field characteristics. The restricted leakage, easier to install and low resistant characteristics are emphasized. The enhanced heat transfer mechanism of Dean Vortex secondary flow is analyzed. A variety of comprehensive efficiency assessments are used. Abstract: An efficient and low resistant circumferential overlap trisection helical baffle shell-and-tube heat exchanger with folded baffles (cothHXf) is presented. It is a modified trisection helical baffle heat exchanger with folded helical baffles for setting rods-and-spanning sleeves. It not only inherits all the merits of circumferential overlap helical baffle scheme, but also adds many additional advantages, such as supporting the inclined baffles with the least rods, simplifying the manufacturing process of spanning tubes and effectively inhibiting the reverse leakage at triangular areas between adjacent baffles. The improved flow characteristic and heat transfer enhancement mechanism of this heat exchanger were numerically investigated in comparison with conventional segmental baffles shell-and-tube heat exchanger (segHX). The flow fields within triangular area of adjacent baffles and nearby regions were depicted. The impacts of the folded baffles on shell-side helical flow, secondary vortex flow, and leakage pattern were analyzed. The distribution configurations of fields of velocity, pressure, temperature and local heat flow rate were revealed. The results show that the heat transfer performance and comprehensive performance evaluation indexes of the cothHXf are much better than those of the segHX while the pressure drop of the cothHXf is much lower than that of the segHX. The numerical simulation results of vivid distributions of flow and thermal fields of the cothHXf can provide theoretical basis for an engineering design and popularized industrial application of the new type heat exchangers.